Quest for the ultimate cardiac CT scanner. Issue 9 (17th July 2017) - FitzGerald, Paul; Edic, Peter; Gao, Hewei; Jin, Yannan; Wang, Jiao; Wang, Ge; Man, Bruno De
Abstract : Purpose: To quantitatively evaluate and compare six proposed system architectures for cardiac CT scanning. Methods: Starting from the clinical requirements for cardiac CT, we defined six dedicated cardiac CT architectures. We selected these architectures based on a previous screening study and defined them in sufficient detail to comprehensively analyze their cost and performance. We developed rigorous comparative evaluation methods for the most important aspects of performance and cost, and we applied these evaluation criteria to the defined cardiac CT architectures. Results: We found that CT system architectures based on the third‐generation geometry provide nearly linear performance improvement versus the increased cost of additional beam lines (i.e., source–detector pairs), although similar performance improvement could be achieved with advanced motion‐correction algorithms. The third‐generation architectures outperform even the most promising of the proposed architectures that deviate substantially from the traditional CT system architectures. Conclusion: This work confirms the validity of the current trend in commercial CT scanner design. However, we anticipate that over time, CT hardware and software technologies will evolve, the relative importance of the performance criteria will change, the relative costs of components will vary, some of the remaining challenges will be addressed, and perhaps new candidate architectures will be identified; therefore, the conclusion of a comparative analysis like this may change. The evaluation methods that we used can provide a framework for other researchers to analyze their own proposed CT architectures.